Knowledge and factors to stop breastfeeding in women of a community in Veracruz, Mexico. - Osorio-Aquino, Marina del Carmen Osorio-Aquino; Landa-Rivera, Ruth Angélica; Blázquez-Morales, María Sobeida Leticia; García-Hernández, Nallely; León-Vera, José Gerardo (Horizonte Sanitario, 2019)
Objetive: Identify the lack of knowledge and completion factors of breastfeeding in women who come to the Health Center of Arroyo Blanco in Xalapa, Veracruz. Materials and methods: Descriptive, cross-sectional study, non-probabilistic sampling at convenience in a sample composing of 31 pregnant women. Results: Results: 96.8% mentioned having knowledge about breastfeeding. However, 12.9% do not know the proper technique for breastfeeding their baby and 22.6% do not know the correct position to perform it. Some factors of completion are: low breast milk production (19.4%) and incorporation into their work (9.7%). Conclusions: Although most women mentioned having knowledge about BF, a considerate proportion reported having lack of knowledge about it, because they do not know the technique and proper position to breastfeed. Insufficient information on breastfeeding, agrees with what was found by Ulunque et al, who point out that the knowledge about breastfeeding in their study by women was insufficient and inadequate. Keywords: Breast feeding; Knowledge; Pregnant Women.